Pengaruh Semangat Kerja Dan Komitmen Kerja Terhadap Kinerja Karyawan PT.PLN (Persero) UP3 Kota Metro - Suwarto; Sugeng; Rahmatiah Ajeng Safitri (Universitas Muhammadiyah Metro, 2025)
This study aims to analyze the effect of work spirit, work commitment on employee performance. This type of research is a quantitative study with a population of 63 employees registered at PT. Pln (Persero) Up3 Metro City only 54 samples used were in accordance with predetermined criteria. The data used is secondary data distribution of questionnaires in the form of a list of questions with several alternative answers for respondents. The statistical test used to test the hypothesis is multiple linear regression analysis and tested using the statistical packages for the social science (SPSS) version 21 program.Based on the results of statistical tests show that Work Discipline, Work Environment has a positive and significant influence on employee performance.